Agronomic evaluation of hemp (Cannabis sativa L.) for cannabidiol production in Yunnan, China - Ouyang, Wenjing; Ou, Jing; Zheng, Qi; Yang, Xiran; Meng, Yuanyuan; Du, Guanghui; Liu, Feihu; Chen, Yuewu; Tang, Kailei (Frontiers in Agronomy, 2025)
IntroductionHemp (Cannabis sativa L.) has gained worldwide attention for its emerging role as a valuable medicinal source, particularly for cannabidiol (CBD) extraction. Yunnan province is currently the only region in China where hemp grown for CBD production is legalized; yet information on optimal agronomic practices for maximizing CBD output in this region remains scarce.MethodsIn the present study, field experiments were conducted in Yunan over two consecutive growing seasons (2019 and 2020) to evaluate CBD productivity and variations in CBD content between female and male plants, as well as among branches along the stem, using a local dioecious hemp cultivar, Yunma #7. Plants were grown under five treatments: a control (CK) with NPK fertilization; additional calcium magnesium phosphate (CK+CMP); and additional boron applied either as powdered boron at the basal stage (CK+CMP+PB1), powdered boron at the budding stage (CK+CMP+PB2), or liquid sugar-alcohol-chelated boron at the budding stage (CK+CMP+LB2).ResultsThe average inflorescence yield reached 4 Mg ha−1, with female plants producing 2.4 Mg ha−1. Inflorescence CBD content averaged approximately 1% (w/w), being 15% higher in female than male plants, and 30% higher in upper than lower inflorescences. Mg and B fertilization showed no statistically significant effects on inflorescence yield and CBD content, the average CBD yield across all fertilization treatments was 20.1 kg ha−1.DiscussionThe study underscores the potential for increasing CBD content through breeding and optimizing harvest methods that distinguish between female and male plants, and separate upper and lower inflorescences.